Biobased particleboards from rice husk and soy protein concentrate: evaluation of flexural properties and dimensional stability under indoor environmental conditions - Mayra C. Chalapud; Emiliano M. Ciannamea; Josefa F. Martucci; Roxana A. Ruseckaite; Pablo M. Stefani (Dyna, 2023)
Biobased particleboards from rice husk (RH) and soybean protein concentrate (SPC) based adhesive were evaluated over 180 days under indoor conditions. Two alternatives were evaluated: the incorporation of carvacrol to the SPC based adhesive, as a natural preservative, and the coating of the RH-SPC based particleboards with a polyurethane lacquer. Coated panels showed the lowest thickness swelling and water absorption at 2 and 24 h of immersion. The modulus of rupture (MOR) increased for the coated panels, while the elasticity modulus (MOE) was the same for all formulations. MOR and MOE obtained for all particleboards evaluated over time met the requirements established by ANSI Standard A208.1 along the 180 days of study. Results showed that particleboard have good physical and mechanical stability under indoor environmental conditions, presenting a good performance at least up to six months.